Hubungan Tingkat Kecemasan dengan Ketergantungan Smartphone pada Remaja di SMP Negeri 27 Palembang: Penelitian - Riko Sandra Putra; Erda Martiani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Smartphone addiction among adolescents can have negative impacts on their mental and social health. This study aims to examine the relationship between anxiety levels and smartphone addiction among adolescents at SMP Negeri 27 Palembang. This research employs a quantitative method with a descriptive survey approach and a cross-sectional design. The study sample consists of 288 respondents selected using a simple random sampling technique. The instruments used include the Zung Self-Rating Anxiety Scale (ZSAS) to measure anxiety levels and the Smartphone Addiction Scale – Short Version (SAS-SV) to assess smartphone addiction. Data analysis was conducted using the chi-square test. The results indicate a significant relationship between anxiety levels and smartphone addiction among adolescents at SMP Negeri 27 Palembang, with a p-value of 0.000 (< 0.05). Based on these findings, educational efforts and interventions are necessary to reduce smartphone addiction and prevent its negative effects on adolescents' mental health.